2024
DOI: 10.3390/v16010157
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Survey on Porcine Parvoviruses (PPV1-7) and Their Association with Major Pathogens in Reproductive Failure Outbreaks in Northern Italy

Giulia Faustini,
Claudia Maria Tucciarone,
Giovanni Franzo
et al.

Abstract: Successful reproductive performance is key to farm competitiveness in the global marketplace. Porcine parvovirus 1 (PPV1) has been identified as a major cause of reproductive failure, and since 2001 new species of porcine parvoviruses, namely PPV2–7, have been identified, although their role is not yet fully understood yet. The present study aimed to investigate PPVs’ presence in reproductive failure outbreaks occurring in 124 farms of northern Italy. Fetuses were collected from 338 sows between 2019 and 2021 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…Possibly, the biosecurity measures adopted in domestic pig farms might have played a relevant role in reducing the introduction and spreading of infectious agents, including PPV7. The proportion of PPV7 infection found in this study was similar to that previously reported in Italy (5.9%) [34], but appeared to be lower than in Poland (19.6%) [32], Southern China (25.73%) [28], Mongolia (28.72%) [10], and the Republic of Korea (14.2%) [48]. Few reports on PPV7 infection in wild boars have been published so far; the positivity percentages found in wild boars in the present work are higher than what was observed by other authors in the Republic of Korea (less than 0.5%) [29].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Possibly, the biosecurity measures adopted in domestic pig farms might have played a relevant role in reducing the introduction and spreading of infectious agents, including PPV7. The proportion of PPV7 infection found in this study was similar to that previously reported in Italy (5.9%) [34], but appeared to be lower than in Poland (19.6%) [32], Southern China (25.73%) [28], Mongolia (28.72%) [10], and the Republic of Korea (14.2%) [48]. Few reports on PPV7 infection in wild boars have been published so far; the positivity percentages found in wild boars in the present work are higher than what was observed by other authors in the Republic of Korea (less than 0.5%) [29].…”
Section: Discussionsupporting
confidence: 91%
“…A study conducted by Miłek et al in Poland [ 32 ], provided the first evidence of detection of PPV7 in domestic pigs in Europe, followed by the report by Blomström et al [ 33 ] in Sweden. More recently, Faustini et al [ 34 ] reported the circulation of PPV7 in domestic pig farms, with reproductive problems in northern Italy in association with other pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation